Ethoxyquin prevents chemotherapy‐induced neurotoxicity via Hsp90 modulation. Issue 6 (December 2013) - Zhu, Jing; Chen, Weiran; Mi, Ruifa; Zhou, Chunhua; Reed, Nicole; Höke, Ahmet
<x xml:space="preserve">Abstract</x> Objective Peripheral neurotoxicity is a major dose‐limiting side effect of many chemotherapeutic drugs. Currently there are no effective disease‐modifying therapies for chemotherapy‐induced peripheral neuropathies, but these side effects of chemotherapy are potentially ideal targets for development of neuroprotective therapies, because candidate drugs can be co‐ or preadministered before the injury to peripheral axons takes place. Methods We used a phenotypic drug screening approach to identify ethoxyquin as a potential neuroprotective drug and carried out additional biochemical experiments to identify its mechanism of action. Results We validated the screening results with ethoxyquin and its derivatives and showed that they prevented paclitaxel‐induced peripheral neuropathy without blocking paclitaxel's ability to kill tumor cells. Furthermore, we demonstrated that ethoxyquin acts by modulating the chaperone activity of heat shock protein 90 (Hsp90) and blocking the binding of 2 of its client proteins, ataxin‐2 and Sf3b2. Ethoxyquin‐induced reduction in levels of both of these proteins resulted in prevention of axonal degeneration caused by paclitaxel. Interpretation Ethoxyquin and its novel derivatives as well as other classes of small molecules that act as Hsp90 modulators may offer a new opportunity for development of drugs to prevent chemotherapy‐induced axonal degeneration. Ann Neurol 2013;74:893–904